The Influence Of Qur’an On Al-Akhtal’s Poetry Ghiyath Ibn Ghawth/ أثر القرآن في شعر الأخطل غياث بن غوث - Alsalamin, Tariq Mohammed (Ijaz Arabi Journal of Arabic Learning, 2025)
The importance of the subject lies in shedding light on the Qur’anic influence on the poetry of Al-Akhtal, the Christian poet. There are differences between finding a Qur’anic influence on a Christian poet, but the Holy Qur’an captured people’s minds with its eloquence and style. The research aims to demonstrate the impact of the Holy Qur’an on Al-Akhtal’s poetry and to represent examples of his poetry in that influence. The study relied on the descriptive analytical method by searching for the Qur’anic verses that influenced Al-Akhtal and employed in a way that completely suited his poetic purposes, the researcher reached a set of results, which are: Al-Akhtal's adherence to his theory was not so much a commitment to his religion and faith as it was a result of his tribal religious heritage, the Holy Qur'an, with its rhetorical miracles and the secret of its artistic beauty, was the best tributary to enrich poets' creativity, deepen their experiences, and imbue them with creative beauty.